Performance Analysis of Object Placement Systems Based on Siemens S7-1200: Evaluation of Effectiveness and Accuracy: Performance Analysis of Object Placement Systems Based on Siemens S7-1200: Evaluation of Effectiveness and Accuracy - Siswoyo, Agus; Artanto, Dian (Jurnal Teknologi, 2023)
The evolution of industrial automation systems has led to innovative solutions for efficient and precise object manipulation. This study introduces a groundbreaking "Object Placement System Based on Siemens S7-1200," designed to enhance object positioning tasks in manufacturing environments. The system's core control unit is the Siemens S7-1200 Programmable Logic Controller (PLC), seamlessly integrated with a network of sensors and actuators for coordinated operations. Operators can easily define target positions and parameters for object placement through a user-friendly human-machine interface. The PLC facilitates real-time data exchange with sensors, enabling accurate object detection and adjustments during placement. The system's implementation involves meticulous PLC programming, sensor integration, and interface design. Experimental results validate its capability to achieve precise and repeatable object placements. The Siemens S7-1200 is a versatile PLC supporting controlled positioning of electrically driven axes and technology objects, tailored for small automation systems requiring simple or advanced Human-Machine Interface (HMI and communication capabilities. The object placement system leverages the capabilities of the S7-1200 PLC for integrated sensor and actuator coordination, ensuring accuracy and repeatability. The study concludes that the innovative system utilizing the Siemens S7-1200 PLC underscores its potential for optimizing production processes and enhancing operational efficiency in industrial automation systems. The demonstrated ability to achieve precise and repeatable object placements highlights the viability of the Siemens S7-1200 platform for advancing object manipulation in industrial settings. The S7-1200 system manual provides specific information about the operation and programming of the PLC. Additionally, the system is supported by the TIA Portal programming software, which offers flexibility and ease of use.